2020
DOI: 10.21714/1984-3925_2020v23n1a6
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Municipal Management in the State of Pará: A Look from the Effectiveness Index

Abstract: Objective: this article seeks to present the levels of management effectiveness of the municipalities in the state of Pará, calculated through the Municipal Management Effectiveness Index (IEGM), composed by seven sectoral indicators: education, health, planning, management fiscal, environmental, citizen protection and information technology and communication governance. Method: the research is characterized as exploratory and the method adopted is bibliographical and documentary analysis. Originality/Relevanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
0
0
Order By: Relevance
“…Consequently, the internal control variables do not explain the IFGF variations. These results disagree with the studies by Leite Filho et al (2018), who noted that municipal transparency, Municipal Development Index, population, gross budget revenue per capita, as well as size, productivity, and collection influence the quality indicator of municipal fiscal management in Brazil; by Silva et al (2020), who found in their study that the location of Brazilian municipalities, the level of human development (IDHM) and fiscal management (IFGF) have a positive relationship with the transparency of Brazilian municipalities; and by Rosa et al (2021), who demonstrate that the balance of fiscal management, measured by the ability to invest, cost of debt, personnel expenses, liquidity, and own revenue, results in a positive impact on municipal performance.…”
Section: Presentation and Analysis Of Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Consequently, the internal control variables do not explain the IFGF variations. These results disagree with the studies by Leite Filho et al (2018), who noted that municipal transparency, Municipal Development Index, population, gross budget revenue per capita, as well as size, productivity, and collection influence the quality indicator of municipal fiscal management in Brazil; by Silva et al (2020), who found in their study that the location of Brazilian municipalities, the level of human development (IDHM) and fiscal management (IFGF) have a positive relationship with the transparency of Brazilian municipalities; and by Rosa et al (2021), who demonstrate that the balance of fiscal management, measured by the ability to invest, cost of debt, personnel expenses, liquidity, and own revenue, results in a positive impact on municipal performance.…”
Section: Presentation and Analysis Of Resultscontrasting
confidence: 99%
“…This may be a possible explanation for the findings of this work, also corroborated by Pinho and Brasil (2021), who state, in their study, that control over public management has gained notoriety, showing signs that society has a great interest in government spending, demanding a better application of public resources and that the acts of public agents are conducted with greater transparency and responsibility. However, the study by Silva et al (2020) highlighted in its observation among municipalities in the state of Pará and through the Municipal Management Effectiveness Index (IEGM), the classification of this index as the worst range (C), demonstrating serious problems in all dimensions assessed, with negative emphasis on institutional aspects such as planning.…”
Section: Presentation and Analysis Of Resultsmentioning
confidence: 99%
“…A noção de eficiência é um valor inerente a qualquer ideia de boa administração. O Estado brasileiro há muito tempo tem incorporado esse valor, visto que ao reestruturar a Administração Pública, por meio do Decreto-Lei nº 200/1967, determina a necessidade de estruturar a administração pública de modo a desempenhar, com eficiência, ações voltadas à satisfação das necessidades da sociedade (Sant'Anna et al, 2019;Silva, Reis, & Ribeiro, (2020). Na década de 90, com a Emenda Constitucional nº 19/1998, a eficiência é elevada à condição de princípio constitucional (art.…”
unclassified